Marketingová strategie pro firmu OHL ŽS, a.s. - Peterková, Eva (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Diplomová práce popisuje vývoj a současný stav ve firmě OHL ŽS, a.s. a je zaměřena na analýzu jejího makroekonomické a mikroekonomické prostředí. Na základě této analýzy navrhuji opatření, která povedou ke splnění požadovaných marketingových cílů.

Master´s thesis describes current economic state of the OHL ŽS, a.s., analyzes the makronomics and mikronomics surrounding. On the basis of this analysis I suggest arrangements that will lead to achieve the required marketing´s targets.
Marketing strategy for company OHL ŽS, Inc.
Keywords: Marketingová strategie; SWOT analýza; STEP analýza; Marketingový mix; Marketing strategy; SWOT analysis; STEP analysis; Marketing mix